2017
DOI: 10.1002/fam.2486
|View full text |Cite
|
Sign up to set email alerts
|

Effects of opening edge treatment and EPS thickness on EPS external thermal insulation composite systems (ETICS) façade reaction‐to‐fire performance based on JIS A1310 standard façade fire test method

Abstract: External thermal insulation composite systems (ETICS) are quite common in constructions. However, the combustible insulation core induces serious fire disasters, especially considering thermoplastic expanded polystyrene (EPS) has been widely used as insulation core. Most of EPS ETICS building fire is caused by window spreading fire. The window opening edge treatment plays an important role in EPS ETICS fire prevention. Presently, in order to investigate optimal opening edge treatment and EPS thickness effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…EPS ETICS specimens were prepared according to the Japanese standard method 15 . All the experiments were conducted in the Building Research of Institute of Japan located in Tsukuba.…”
Section: Experiments and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…EPS ETICS specimens were prepared according to the Japanese standard method 15 . All the experiments were conducted in the Building Research of Institute of Japan located in Tsukuba.…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…The radiation heat from a combustion flame has been reported to show a heavily influence on the accuracy of temperature measurement during large‐scale fire test 20 . The radiation heat flux profiles of EPS ETICS façade surface during JIS A 1310 test indicated heat flux density of location HF1 (0.5 m) and HF2 (0.9 m) are much higher than other position 15 . Therefore, radiation heat perhaps arise the uncertainty of thermocouples.…”
Section: Experiments and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, as the façade fire attracts more and more attentions, the investigation into window fire plume is a popular topic for fire researchers. The 2009 CCTV Tower Fire and 2010 Shanghai Fire in China are typical cases of large façade fire . Especially after London Grenfell Tower façade fire happened on June 14, 2017, the attention was increased sharply .…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the assumption that the width of the flame is constant, Thomas and Law 6 proposed a semiempirical formula to predict the height and length of the ejected flame from a compartment. Zhou et al, 7 found that EPS ETICS with back‐wrapping method performed well in mitigating the severity of window spreading fire. In recent years, a series of important researches on the ejected plume behavior was established by Michael A. Delichatsios and Lee Yee‐Ping 8,9 .…”
Section: Introductionmentioning
confidence: 99%